Personal Financial Management Among University Students and Its Impact on Consumeristic Behavior - Tria Feri Ardona; Siti Aisatul Khumairoh; Fitra Asra Muliani D. (Universitas Islam Negeri Raden Mas Said Surakarta, 2025)
Objective: This study aims to examine how students manage personal finances within a digitally driven culture and to analyze the extent to which financial literacy and social media exposure influence consumptive behavior and impulsive buying tendencies. Method: The research employs a qualitative-analytical approach through a critical review of recent empirical literature, interpreted using contemporary frameworks of digital consumer behavior that integrate economic, psychological, social, and digital perspectives. Result: The analysis shows that students’ consumptive behavior is shaped not only by limited financial literacy but also by algorithm-driven digital environments, social media pressures, weak self-control, and the internalization of digital lifestyle values. The accessibility of online transactions and pay-later services further blurs the boundary between needs and wants, intensifying consumption beyond students’ financial capacity. Conclusion: The study proposes a contextualized financial literacy framework for Gen Z that integrates cognitive, emotional, and social dimensions. Strengthening financial education through holistic and digitally responsive approaches is essential for universities and educational institutions to promote healthier, more sustainable financial habits among students in the contemporary digital ecosystem.